Hubungan Masyarakat dan Budaya Lokal dalam Interaksi Sosial Masyarakat - Fatonah, Ratih; Irma, Irma; Maulana, Muhammad Zidan; Yasin, Muhammad (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2024)
The existence of Gang Hikmah on Jalan Hidayatullah Sangatta Utara as an urban environment with a diversity of communities and local cultural values is an interesting research arena for understanding the dynamics of the relationship between society and local culture. In this context, the role of local culture in shaping social interaction becomes important for understanding identity and social integration. This research aims to answer key questions, including: What is the relationship between society and local culture in Gang Hikmah Hidayatullah Sangatta Utara? What is the process of social interaction between the community and local culture in Gang Hikmah Hidayatullah, Sangatta Utara? What are the supporting and inhibiting factors in social interaction between the community and local culture in Gang Hikmah Hidayatullah, Sangatta Utara? This research uses descriptive and qualitative research methods. Research data was taken from observations, interviews, and documentation. The results of research at Gang Hikmah Hidayatullah Sangatta Utara show that local culture in Gang Hikmah has a significant impact on the community's social interaction patterns. Factors such as cooperation, local culture, and communal activities are positive drivers for strengthening social ties. However, there are societal gaps in social interaction caused by individual busyness or work, which creates obstacles to creating balanced relationships.